2020
DOI: 10.1002/cbdv.202000155
|View full text |Cite
|
Sign up to set email alerts
|

LC‐ESI‐QTOF‐MS for the Profiling of the Metabolites and in Vitro Enzymes Inhibition Activity of Bryophyllum pinnatum and Oxalis corniculata Collected from Ramechhap District of Nepal

Abstract: The objective of this study was to profile the chemical components and biological activity analysis of crude extract of Bryophyllum pinnatum and Oxalis corniculata. Results revealed that the analyzed plant materials encompass the high amount of total phenolic and flavonoids content and have significant antioxidant activities. Furthermore, methanol extracts are the potential source of α‐amylase, α‐glucosidase, lipase, tyrosinase and elastase inhibitors. High resolution mass spectrometry revealed the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Despite the growing number of studies describing pharmacological actions of Kalanchoe extracts, and the knowledge about flavonoids as important chemical constituents in this genus, most of the studies have just reported the presence of these molecules, without properly investigating their bioactive behavior. Indeed, several of these studies only suggest the potential role of flavonoids in a given activity [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], without assessing the isolated compound to confirm its bioactivity. The characterization of bioactive compounds is important not only to define the molecules responsible for a given biological property, but also for the development of phytomedicines.…”
Section: Main Classes Of Bioactive Compounds In Kalanchoe ...mentioning
confidence: 99%
“…Despite the growing number of studies describing pharmacological actions of Kalanchoe extracts, and the knowledge about flavonoids as important chemical constituents in this genus, most of the studies have just reported the presence of these molecules, without properly investigating their bioactive behavior. Indeed, several of these studies only suggest the potential role of flavonoids in a given activity [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], without assessing the isolated compound to confirm its bioactivity. The characterization of bioactive compounds is important not only to define the molecules responsible for a given biological property, but also for the development of phytomedicines.…”
Section: Main Classes Of Bioactive Compounds In Kalanchoe ...mentioning
confidence: 99%
“…Scavenging, Chlorophyll, and Carotenoid Contents. Te estimation of favonoids, phenolics, scavenging, and chlorophyll contents were done using standard protocols as done by various researchers [56][57][58].…”
Section: Estimation Of the Change In Flavonoid Phenolics Radicalmentioning
confidence: 99%
“…Each serving had 7.76 mg of gallic acid equivalents and 6.92 mg of rutin equivalents, respectively, in the total phenol content. [16][17][18] The water extracts included a high concentration of tannins, palmitic acid, and a mixture of oleic, linoleic, linolenic, and stearic acids, while the alcoholic extract contained carbohydrates, glycosides, phytosterols, phenolic compounds, amino acids, and stearic acid. The sample also included calcium, fiber, and tannin, according to the research.…”
Section: Phytochemical Profilementioning
confidence: 99%